Anxiety levels and methods of coping with stress of adolescents undergoing their first gynecological examination - Gulbahtiyar Demirel; Sukran Ertekin Pinar; Dilek Bilgic (Journal of Psychosomatic Obstetrics and Gynecology, 2020)
Objective: The present study was conducted to assess the anxiety levels and the methods of coping with the stress of adolescents who underwent their first gynecological examination. Methods: The sample of this descriptive study consisted of 223 married or single adolescent women who went to a state hospital in Sivas Province in Turkey for their first gynecological examination. The data were collected by face-to-face interviews with the Personal Information Form, the State Anxiety Inventory (SAI) and the Ways of Coping Inventory (WCI). Results: There was a statistically significant negative correlation between the SAI scores, and the self-confident approach (r = −0.305; p = 0.001) and optimistic approach (r = −0.170; p = 0.011) of the WCI subscales. A statistically significant positive correlation was found between SAI scores, and the desperate approach (r = 0.153; p = 0.022) and submissive approach (r = 0.143; p = 0.032). Conclusion: Adolescent women who underwent their first gynecological examination have “moderate” levels of anxiety and their coping with stress styles are ineffective. As anxiety levels increase, they use more ineffective methods.